2017
DOI: 10.1155/2017/5245904
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine Induced Lupus Syndrome Presenting with Recurrent Pericardial Effusion and a Negative Antinuclear Antibody

Abstract: Drug induced lupus erythematosus (DIL or DILE) is an autoimmune disorder caused by chronic use of certain drugs. We report a unique case of hydralazine induced lupus syndrome (HILS) with a negative antinuclear antibody in a female patient who was on hydralazine for a period of 1.5–2 years and developed recurrent pericardial effusion as a result of it. Initially her condition was managed with a pericardial window. The recurrence of a massive pericardial effusion necessitated a right hemipericardiectomy. After h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…HILS should be suspected in any patient on hydralazine presenting with unexplained effusion; moreover, in our patient, additional laboratory evidence revealed the presence of active lupus, including low C3, elevated ESR and CRP, pancytopenia, negative anti-dsDNA, and positive anti-histone antibody ( 5 ). We believe the clinical picture and laboratory findings of our patient were consistent with the presentation of HILS with negative ANA ( 3 , 4 ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…HILS should be suspected in any patient on hydralazine presenting with unexplained effusion; moreover, in our patient, additional laboratory evidence revealed the presence of active lupus, including low C3, elevated ESR and CRP, pancytopenia, negative anti-dsDNA, and positive anti-histone antibody ( 5 ). We believe the clinical picture and laboratory findings of our patient were consistent with the presentation of HILS with negative ANA ( 3 , 4 ).…”
Section: Introductionsupporting
confidence: 81%
“…Positive antinuclear antibody (ANA) serology is the standard for SLE and DILS diagnosis. In the literature, only two cases so far have described an unusual presentation of HILS with negative ANA ( 3 , 4 ). In both these cases, patients presented with pericardial effusion.…”
Section: Introductionmentioning
confidence: 99%
“…One of its more infrequent presentations reported in medical literature is pericardial effusion reported at <5% [ 2 ]. As per our literature review, this is the second case of hydralazine causing DILE with a negative ANA [ 3 ].…”
Section: Introductionmentioning
confidence: 96%
“…Previous hydralazine PK studies reported nonlinearity with single doses higher than 100-150 mg. 9 Because both pharmacological activity and toxicity are attributed to parent drug exposure, caution is suggested with high-dose hydralazine during pregnancy. [54][55][56] Adverse effects and complications when parenteral hydralazine is needed during pregnancy include placental abruption, increased risk of surgical delivery, maternal oliguria, altered fetal heart rate, and low Apgar scores at 1 minute. 57 NAT2 slow acetylators, especially in female patients, have been found to have increased risk of developing severe adverse events (eg, systemic lupus erythematosus) with highdose hydralazine (>200 mg/day).…”
Section: Discussionmentioning
confidence: 99%